Status and Potential for Ecosystem-Based Fisheries Management in Tempe Lake, Indonesia: An Ecosystem Approach to Fisheries Management (EAFM) - Haerunnisa, Haerunnisa; Kurniawan B, Agus; Budimawan, Budimawan; Burhanuddin, Iqbal (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2025)
The critical condition of Lake Tempe has undergone comprehensive changes over the last 10 years. Fisheries management strategy indicators with an appropriate ecosystem-based approach can reduce and prevent unbalanced environmental impacts. This research analyzes fisheries management using the Ecosystem Approach Fisheries Management (EAFM) module, the Rapid Appraisal for Fisheries Sustainability (RAPFISH) method. Six important statuses and dimensions used as attribute indicator analysis in this research are fish resource dimensions, habitat dimensions, fishing technique dimensions, economic dimensions, social dimensions, and institutional dimensions. The analysis results show that the fishery management status value for Lake Tempe is 36.072 in the unsustainable category. Based on the RAPFISH analysis, namely: (1) Economic dimensions 21.390 in the unsustainable category, (2) Habitat dimensions 36.050 in the unsustainable category, (3) Fish resource dimensions 24.483 in the moderately sustainable category, (4) Fishing technique dimensions 42.180 in the moderately sustainable category, (5) Institutional dimensions 48.070 categories are quite sustainable (6) Social dimensions 45.590 categories are quite sustainable. Based on the AHP analysis, habitat dimensions, protection of important zones for spawning grounds, nursery grounds, and water hyacinth cover problems are identified.